Strain rate imaging after dynamic stress provides objective evidence of persistent regional myocardial dysfunction in ischaemic myocardium: regional stunning identified?. Issue 2 (18th January 2005) - Williams, R I; Payne, N; Phillips, T; D'hooge, J; Fraser, A G
Abstract : Objective: To investigate whether persistent ischaemic dysfunction of the myocardium after dynamic stress can be diagnosed from changes in ultrasonic strain rate and strain. Design: Prospective observational study, with age matched controls. Setting: University hospital. Patients and methods: 26 patients (23 men, mean (SD) age 58.9 (8.1) years) with coronary artery disease but no infarction and 12 controls (9 men, aged 56.1 (8.8) years) with normal coronary arteriography and negative exercise test underwent treadmill exercise (Bruce protocol). Tissue Doppler echocardiography was performed at baseline, at peak exercise, and at intervals up to one hour. Systolic and diastolic velocity, strain, and strain rate were recorded in the basal anterior segment of 16 patients with proximal left anterior descending coronary artery disease. Results: Patients developed ischaemia, since they experienced angina, exercised for less time, and reached a lower workload than the control group, and had ST segment depression (−2.4 mm). Myocardial systolic velocity immediately after exercise increased by 31% and strain rate fell by 25% compared with increases of 92% and 62%, respectively, in the control group (p < 0.05). During recovery, myocardial systolic velocity and strain rate normalised quickly, whereas systolic strain remained depressed at 30 and 60 minutes after exercise, by 21% and 23%, respectively, compared with baseline (p < 0.05 versus controls). Myocardial diastolic velocities and strain rate normalised but early diastolic strain remained depressed by 32% compared with controls for 60 minutes (p < 0.05). Strain during atrial contraction was abnormal for 30 minutes. Conclusions: Myocardial strain shows regional post-ischaemic dysfunction in systole and diastole and may become a useful diagnostic tool in patients presenting with chest pain with a normal ECG.